Changes of composition and content of tricyclic terpane, hopane, sterane, and aromatic biomarkers throughout the oil window: A detailed study on maturity parameters of Lower Toarcian Posidonia Shale of the Hils Syncline, NW Germany. (December 2019) - Fang, Ronghui; Littke, Ralf; Zieger, Laura; Baniasad, Alireza; Li, Meijun; Schwarzbauer, Jan
Highlights: Systematic evaluation of biomarker maturity parameters and their ranges. Aromatic maturity parameters mirror maturation in and beyond oil window very well. Strong concentration decrease of non-aromatic and aromatic polycyclic biomarkers within oil window. Only weak weathering of cores after 40 years of dry storage. Abstract: A total of 30 core samples of organic matter-rich Lower Toarcian shale (Posidonia Shale) were geochemically analyzed to study systematic changes in the quantitative and qualitative composition of specific biomarkers at different thermal maturities ranging from 0.48 to 1.45% vitrinite reflectance (VRr ). The samples are derived from 5 wells (Hils Syncline, NW Germany) each representing a different level of maturation (0.48, 0.68, 0.73, 0.88, 1.45 %VRr ). In NW Germany, Posidonia Shale was deposited under marine, oxygen-deficient bottom water containing initially high amounts of TOC (above 10%) and marine type I-II kerogen. Upon maturation, organic carbon has been lost and hydrogen index values have decreased. Biomarker ratios reflecting this maturation very well include ratios of short over long-chain n -alkanes, ratios of pristane and phytane over n C17 and n C18, Ts/(Ts + Tm), C29 Ts/(C29 Ts + C29 H), ratios based on DMDBTs, and TA(I)/TA(I + II) ratios (triaromatic steroids). The evolution of different steroid-, hopane-, naphthalene-, phenanthrene- and dibenzothiophene-related parameters is documented and compared to literature. Concentrations of individual hydrocarbons were measured in order to obtain quantitative data on biomarker abundance and their evolution upon maturation. Whereas there is a general trend of increasing biomarker content from immature (0.48 %VRr ) to early mature (0.68 %VRr ) conditions and of decreasing biomarker content with maturation from 0.68 to 0.88 %VRr, there are some exceptions from this trend, especially at low levels of maturity. Almost no polycyclic biomarkers were detected at the highest maturity level of 1.45 %VRr in well Haddessen, where n -alkanes and aromatic hydrocarbons are predominant. The overall pattern of polycyclic biomarker abundance is not only determined by isomerization and aromatization processes, but mainly by preferential degradation of thermally less stable biomarkers leading to the observed modifications of biomarker maturity parameters. Furthermore, outer and inner sections from the 10 cm wide cores were compared in order to find out, whether 40 years of dry storage in a core repository affected the biomarker parameters. No significant and systematic differences have been observed, with exception of the most mature Haddessen well, where low molecular weight n -alkanes (< n C21 ) are more abundant in the outer part.